Tolerability, Safety, and Pharmacokinetics of Ivermectin After Nasal Application in Healthy Adult Subjects. - Wissel, Stefan; Wissel, Philipp; Rischer, Matthias; Häberlein, Felix; Riethmüller‐Winzen, Hilde; Häberlein, Hanns (Journal of Clinical Pharmacology, 2026)
Nasal epithelium is the site of infection for SARS‐CoV2 viruses, with interactions of the viral spike protein with the ACE2 receptor of the host cell. Molecular docking studies have shown that ivermectin shields the spike protein and thereby prevents binding to ACE2. Nasal application of high doses of ivermectin could be the right therapeutic approach in the treatment and prevention of COVID‐19. Tolerability, safety, and pharmacokinetics of ivermectin, administered nasally as 5% microsuspension (F004), were investigated in a randomized, double‐blind, parallel‐groups, placebo‐controlled phase 1 study in 28 healthy adults. Bioavailability of a single dose of 14 mg ivermectin was determined with AUC0–tT of 1701.1 ng/mL h (AUC0–∞ of 2382.7 ng/mL h, calculated), Cmax of 96.2 ng/mL, Tmax of 4.4 h, and T1/2 of 59.9 h. Following 42 mg/day multiple dose (3 × 14 mg every 6 h) administered nasally over 5 days, AUC0‐∞ of 2194.4 ng/mL h was analyzed, and 96% of ivermectin concentrations were still measurable 12 h after the last dose. F004 was safe in this study and well‐tolerated. Nine (F004 group) and three (placebo group) of 28 subjects reported 14 symptoms, including a few systemic but mainly local nasal adverse events (AE). The number of subjects reporting AE decreased continuously after both F004 and placebo treatment. All subjects recovered fully with no AE recorded at the end of the study. Nasal examination showed stable patterns of nasal mucosal grading, mucosal bleeding, and crusting of the mucosa. Nasally administered ivermectin is well tolerated in high concentrations and could provide systemic therapeutic benefits in addition to local effects.